Relationship of Mineralogy and Paleoenvironments in the Late Pleistocene Kalimati to Sunakothi and Thimi Formations, Kathmandu Basin, Central, Nepal - Paudel, Mukunda Raj (Journal of Institute of Science and Technology, 2015)
The investigation was carried out on mineralogical composition of the three different stratigraphic units of the Kathmandu Basin-fill sediments. On the basis of the variation of the non-clay and clay fraction, here the investigation was interpreted to establish the paleoenvironmental and paleoclimatic condition during the deposition from the lacustrine facies of the Kalimati Formation to the fluvio-lacustrine facies of the Sunakothi Formation and probable caused of these change. Both Kalimati and Sunakothi sediments contain same mineral composition while Thimi sediments did not contain carbonate (calcite) minerals and amount of mica is higher than the Sunakothi and Kalimati sediments. Higher amount of smectite within the clay fraction and presence of calcite within both clay and non-clay fraction in the basal part of the Sunakothi Formation indicates seasonal and prolong dry climatic condition occurred during the deposition of the Kalimati Formation to Sunakothi Formation. On the other hand, lower amount of kaolinite/smectite ratio, and excess amount of carbonate mineral within the basal part of the Sunakothi Formation shows depositional environmental changes from deep to shallow, and lake water became more alkaline. Gradually lacustrine condition changes into the fluvio-lacustrine condition. On the other hand, higher ratio of the kaolinite/smectite within the Kalimati Formation to lower ratio of the kaolinite/smectite within the basal part of the Sunakothi Formation indicates that climatic condition was more seasonal and cold/ dry than the Kalimati Formation. Both kaolinite/smectite and smectite/illite value indicate paleoprecipitation of the Kathmandu valley, was higher during the Kalimati phase than the Sunakothi. Journal of Institute of Science and Technology, 2014, 19(1): 86-95